QTL analyses for seed iron and zinc concentrations in an intra-genepool population of Andean common beans (Phaseolus vulgaris L.) - Blair, Matthew W.; Astudillo, Carolina; Rengifo, J; Beebe, Stephen E.; Graham, R (Springer, 2011)
Legumes provide essential micronutrients that are found only in low amounts in the cereals or root crops. An ongoing project at CIAT has shown that the legume common bean is variable in the amount of seed minerals (iron, zinc, and other elements), vitamins, and sulfur amino acids that they contain and that these traits are likely to be inherited quantitatively. In this study we analyzed iron and zinc concentrations in an Andean recombinant inbred line (RIL) population of 100 lines derived from a cross between G21242, a Colombian cream-mottled climbing bean with high seed iron/zinc and G21078, an Argentinean cream seeded climbing bean with low seed iron/zinc. The population was planted across three environments; seed from each genotype was analyzed with two analytical methods, and quantitative trait loci (QTL) were detected using composite interval mapping and single-point analyses. A complete genetic map was created for the cross using a total of 74 microsatellite markers to anchor the map to previously published reference maps and 42 RAPD markers. In total, nine seed mineral QTL were identified on five linkage groups (LGs) with the most important being new loci on b02 and other QTL on b06, b08, and b07 near phaseolin. Seed weight QTL were associated with these on b02 and b08. These Andean-derived QTL are candidates for marker-assisted selection either in combination with QTL from the Mesoamerican genepool or with other QTL found in inter and intra-genepool crosses, and the genetic map can be used to anchor other intra-genepool studies.